Structural and luminescence study of Dy3+ doped phosphate glasses for solid state lighting applications - M. Shoaib (2020)
© 2020 Elsevier B.V. The present study reports the preparation and analysis of physical, luminescence and structural properties of Dy2O3 doped phosphate glasses. The density and refractive index demonstrate increasing tendency as Dy2O3 concentration increased. The luminescence concentration quenching point is observed at 1.0 mol% of Dy2O3 and 17 mol% of Gd2O3 concentration, when monitored at 350 nm and 275 nm respectively. Similarly, the Judd-Ofelt (JO) theory used to calculate JO intensity parameters (Ω2, Ω4 and Ω6). These parameters show Ω2>Ω4>Ω6 trend. It is recorded that 4F9/2 → 6H13/2 transition has higher values of transition probabilities, branching ratio and emission cross-section parameters. The calculated and experimental results for the radiative properties were compared with each other and with previous reported studies. The decay time is obtained with the emission and excitation of 573 and 350 nm respectively and it is found that, the decay time decreases with increasing Dy3+ concentration. Photoluminescence decay curve analysis and Radio luminescence (X-ray source) decay curve analysis was analyzed. The prepared samples were studied through XANES and EXAFS analysis to understand the local environment of Gd and Dy atom. Gadolinium and Dysprosium show +3 oxidation states in the present glass. Bond distance of Gd–O and Gd–Gd decreases with increase in Gd2O3 content.